Impact of prior exposures on biomarkers of blast during military tactical training - Wang, Zhaoyu; Sun, Shengnan; Liu, Qingkun; Kranfli, Alis Askar; Nemes, Jeffrey; Sullan, Molly; Hoisington, Andrew; Brenner, Lisa A.; Skotak, Maciej; LaValle, Christina R.; Ge, Yongchao; Carr, Walter; et al. (Frontiers in Neurology, 2025)
IntroductionBlast injuries and subclinical effects are of significant concern among those Service Members (SMs) participating in military operations and tactical trainings. Studies of SMs repeatedly exposed during training find concussion-like symptomology with transient decrements in neurocognitive performance, and alterations in blood biomarkers. How prior mild TBI (mTBI) history interacts with low-level blast (LLB) exposure, however, remains unexplored, which we investigate in the present study, to identify interindividual biomarker changes from LLB exposures influenced by prior history of mTBI.MethodsGene transcript and amyloid-beta (Aβ40 and Aβ42) protein levels were assayed using timeseries blood specimens collected at pre-blast, post-blast (within ~1 h), and follow-up-blast (~16 h) after LLB exposure for 30 SMs (age 30.3 ± 7.5) via RNA-seq and Single Molecule Array (SIMOA). Statistical models with timepoint and mTBI status interaction adjusted for age were used, and p-values adjusted for multiple testing.ResultsWe found enrichment of genes involved in blood brain barrier, inflammatory, and immune responses associated with blast exposure, with significant elevated expression of target genes among SMs with mTBI history. Levels of Aβ40 and Aβ42 did not differ pre-blast vs. post/follow-up-blast LLB exposure when comparing SMs by prior mTBI history. Aβ40 and Aβ42 levels were significantly decreased in response to blast at the follow-up (~16 h) LLB exposure timepoint, concomitant with elevated expression of genes involved in amyloid-beta regulation and clearance in SMs with mTBI.ConclusionFindings show inter-individual differences in biomarker levels following exposures to blast that may be attributed to prior mTBI history.